2004
DOI: 10.1016/j.neuron.2004.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Genetically Determined Visuospatial Construction Deficit in Williams Syndrome

Abstract: A unique opportunity to understand genetic determinants of cognition is offered by Williams syndrome (WS), a well-characterized hemideletion on chromosome 7q11.23 that causes extreme, specific weakness in visuospatial construction (the ability to visualize an object as a set of parts or construct a replica). Using multimodal neuroimaging, we identified a neural mechanism underlying the WS visuoconstructive deficit. Hierarchical assessment of visual processing with fMRI showed isolated hypoactivation in WS in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
301
4
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(355 citation statements)
references
References 40 publications
47
301
4
3
Order By: Relevance
“…These include the hippocampal formation, IPL, amygdala, and OFC (12,14,17,20,(23)(24)(25)(26)(27)(28)30). Such transmodal cortical systems (51) are composed of subregionally specialized and highly interconnected heteromodal, paralimbic, and limbic cortices (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the hippocampal formation, IPL, amygdala, and OFC (12,14,17,20,(23)(24)(25)(26)(27)(28)30). Such transmodal cortical systems (51) are composed of subregionally specialized and highly interconnected heteromodal, paralimbic, and limbic cortices (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…These mouse studies also documented alterations in fear response [for both LIMK1 and GTF2IRD1 (20,22)] and reduced aggression [for GTF2IRD1 (22)]. In parallel with these preclinical observations, research on the neural mechanisms underlying WS-specific behavioral characteristics has identified functional and structural alterations of the intraparietal sulcus (12,(23)(24)(25)(26), hippocampal formation (27), amygdala, and orbitofrontal cortex (OFC) (12,17,28), and aberrant orbitofrontal circuitry has been associated with the syndrome's distinctive pattern of emotional processing: remarkable lack of social fear coupled with a high incidence of nonsocial anxieties and phobias (17,29,30).…”
mentioning
confidence: 91%
“…Our methods for model fitting, selection and evaluation have been described previously. 42 Briefly, models were fitted from eigenvariates 43 using the software package Mx (http://www.vcu.edu/mx/). Activity from vmPFC, perigenual cingulate and bilateral amygdala was extracted from anatomical masks for all male participants.…”
Section: Functional Connectivity Analysesmentioning
confidence: 99%
“…areas of increased cell packing, neuronal size differences), when compared to control brains. MRI studies report increased gyrification (cortical folding) in WS in the right parietal and occipital lobes (Schmitt et al, 2002), and a disproportionate reduction in parietaloccipital regions (Meyer-Lindenberg et al, 2004;Reiss et al, 2000;. At a functional level, ERP investigation has shown that individuals with WS can group by closure, but that this is associated with deviant neural processing in the temporaloccipital areas (Grice et al, 2003).…”
Section: Experimental Trialsmentioning
confidence: 99%